The Maturity of Lecturerâs Self Reflection as Tutor to The Paradigm of Teacher Centered Learning and Student-Centered Learning in Tutorials - Burhanudin, Afif; Pamungkasari, Eti Poncorini; Timor, Amandha Boy (Nexus Pendidikan Kedokteran dan Kesehatan, 2017)
Introduction: In 2007 the learning system in Faculty of Medicine of Universitas Sebelas Maret changed to Student Centered Learning, which the role of lecturer changed to tutor who facilitated student to get information. From this change, it had a paradigm shift. This research aimed to know about the difference of tutorâs self assessment between tutor with teacher centered learning paradigm and student-centered learning. Methods: This research was an obersevational research with cross sectional approach. Research was conducted on Desember 2016 at Faculty of Medicine Sebelas Maret University Surakarta. Total subject was 85 respondent using total sampling technique with inclusions and exclusions criterias. Data was computed and analyzed using Independent t-test analysis. Results: Statistical analysis was performed using Independent t-test analysis resulting p-value 0.631. The analysis from both of the variable showed p-value >0.05, hence, there is no significant difference of tutorâs self assessment between tutor with teacher centered learning paradigm and student-centered learning paradigm. Conclusions: There was no significant difference of tutorâs self assessment between tutor with teacher centered learning paradigm and student-centered learning paradigm. Keywords: Paradigm Shift, Tutorâs Self Assesment, TutorÂ